Physicians’ Portraits Defining Medical Progress in Europe - Brabin , Bernard (Medicina Historica, 2025)
Over four centuries painted portraits of European doctors gave insights into our medical past.   Throughout the 20th century European Nations extended this tradition to the general public through their Postal Administrations. This paper collates philatelic medical portraiture for nineteen European states since 1927, when the first such stamps were issued. The aim was to collate and identify the criteria for selecting medical doctors for national representation. A systematic search identified portrait stamps of 270 doctors either born or graduating in medicine from those countries, representing early Greek to modern medicine. Most portrait stamps featured doctors practicing in the 19th century. France released the highest number of portrait stamps (n=42) and Turkey the lowest (n=7). The issue rate per million population was highest for Austria (2.52) and lowest for Turkey (0.08), and Great Britain (0.10), which was surprising given its distinguished medical record.  In comparing countries, the stature of individuals was assessed by the number of times they were celebrated by the home country or featured on stamps from other European countries. Personal honours, including Nobel prizes, were noted, and short biographies of some notable individuals are described. Only ten female physicians were assigned portrait stamps and while some doctors were revered rather for non-medical achievements such as literature and politics, many distinguished doctors were ignored. Medical knowledge was pioneered and publicized in the past by individual’s portraits on stamps. Fewer portrait stamps are now issued, with current emphasis mostly on illustrating scientific teams. Arguably medicine, science and society still need portrayal of their famous physicians.